Penerapan Model Pembelajaran Kooperatif MURDER untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas VIII Binsus (Bimbingan Khusus) B SMP Muhammadiyah 2 Pekanbaru - Herlina, Yolanda; Indriati, Mefa; Suripah; Wahyuni, Astri (Papanda, 2025)
This study aims to see how the mathematics learning outcomes of class VIII Binsus (Special Guidance) B students of Muhammadiyah 2 Pekanbaru Middle School use the MURDER cooperative learning model. This study uses the classroom action research (CAR) method through two cycles, each cycle consisting of four stages, namely: Planning Stage, Acting Stage, Observation Stage, and Reflection Stage. The subjects of the study were Class VIII Binsus B of Muhammadiyah 2 Pekanbaru Middle School with a total of 22 students consisting of 11 male students and 11 female students. Data in this study were collected through observations of Teacher & Student Activity Observation Sheets and Mathematics Learning Outcomes Tests. The results of the study indicate that the application of the MURDER cooperative learning model can improve students' mathematics learning outcomes. This can be seen from the increase in the average value of student learning outcomes and the percentage of classical completeness from the basic score to cycle I and from cycle I to cycle II. The average learning outcomes before being given action on the basic score only reached an average value of 71% with a classical completeness of 45%. The average learning outcomes after being given action in cycle I for daily test I experienced an increase above the basic score, namely the average value reached 74% with a classical completeness of 68%. In cycle II daily test II, the average student learning outcomes after being given action also experienced a higher increase than the daily test I in cycle I, namely the average value reached 81% with a classical completeness of 77%. Thus, it can be concluded that the application of the MURDER cooperative learning model is effective in improving the mathematics learning outcomes of class VIII B students of SMP Muhammadiyah 2 Pekanbaru.